The future of biological nitrogen fixation in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The next congress of the African Association for Biological Nitrogen Fixation 'Challenges and Imperatives for BNF Research and Application in Africa for the Twenty-first Century', will be held from 25 to 29 September in Nairobi, Kenya. Organising...